Shards & Waterfalls New choreography invades the Royal Opera House - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 2004)
New York invades the Royal Opera House. Guillem's killer instinct told her it was time to muscle in on male territory. Bare-chested in skimpy underwear, Watson opens Qualia with a temper tantrum of a solo that grabs attention by the throat. PALABRAS CLAVE: Royal Ballet, Mark Morris, Gong, William Tuckett, Proverb, Russell Maliphant, Broken Fall, Wayne McGregor, Symbiont(s).